2017
DOI: 10.2174/1874205x01711010092
|View full text |Cite
|
Sign up to set email alerts
|

Successful Nonoperative Treatment of a Lumbar Spine Extension Injury with Disruption of all Three Bony Columns in a Patient with Ankylosing Spondylitis – A Case Report

Abstract: Study Design:A case report.Background:Patients with ankylosing spondylitis have altered spinal biomechanics putting them at increased risk of spinal fractures that are unstable. As a result there is an increasing trend to treat these fractures with surgical stabilization. We hypothesize that the fracture pattern is also an important factor in patients with this disease and that those with an extension injury in the lumbar spine can be treated with brace immobilization.Objective:Report on the non-operative mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ischia is the most common complication (13 cases). It was found that fracture dislocations showed a higher incidence of neurological injuries than other spinal fractures [ 1 , 2 ]. Lumbar injury is a common clinical disease and frequently occurring disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ischia is the most common complication (13 cases). It was found that fracture dislocations showed a higher incidence of neurological injuries than other spinal fractures [ 1 , 2 ]. Lumbar injury is a common clinical disease and frequently occurring disease.…”
Section: Introductionmentioning
confidence: 99%